2021
DOI: 10.1177/03611981211033278
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fatal Truck-Involved Work Zone Crashes in Florida: Application of Tree-Based Models

Abstract: This paper presents the results of an analysis focusing on large truck-involved work zone fatal crashes using seven-year crash data in the State of Florida. Decision tree/random forest models were applied to specifically detect critical crash patterns that result in a fatality outcome. Because of the imbalanced nature of crash severity data (very low frequency of fatal crashes compared with property damage only or injury), data were treated using random and systematic over-sampling techniques. Marginal effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…The choice of adopting SMOTE, consistent with Orsini et al (3), was mainly because of the limited sample size available, which would have made RUMC unfeasible, in particular for short data collection durations. It is also worth noting that the practice of using SMOTE is becoming quite established in road safety modeling, and many recent works have applied it with good results (22)(23)(24)(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%
“…The choice of adopting SMOTE, consistent with Orsini et al (3), was mainly because of the limited sample size available, which would have made RUMC unfeasible, in particular for short data collection durations. It is also worth noting that the practice of using SMOTE is becoming quite established in road safety modeling, and many recent works have applied it with good results (22)(23)(24)(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%
“…However, using traditional resampling techniques like RUMC can result in the loss of crucial information [23,32]. Consequently, it is vital to explore synthetic resampling strategies as an alternative approach to effectively tackle this issue [33][34][35][36]. Despite the potential benefits of synthetic resampling strategies, comprehensive comparative analyses assessing the predictive power of parametric and non-parametric machine learning techniques in conjunction with such strategies remain scarce.…”
Section: Applications Of Machine Learning Models In Crash Severity Pr...mentioning
confidence: 99%
“…Regarding the influence of weather and lighting conditions on crash severity, the results in the literature are inconsistent. It should be noted that while some studies ranked the weather and lighting conditions as one of the main predictors of the crash severity outcome [19,31,75], others are in accordance with the findings of this paper, indicating the insignificance of these variables on crash severity [23,35]. In addition, the significance of the temporal factors has been confirmed in the literature of subject as Zheng et al [19] identified the importance of time of day and weekday in the severity levels of crashes involving trucks.…”
Section: Plos Onementioning
confidence: 99%